(untitled) (Zien Journal of Social Sciences and Humanities, 2023)
Underground communication networks play a crucial role in today’s world as they facilitate communication and data transfer between different locations, including homes, businesses, and government entities. To deploy these networks, modern methods are being used that are faster, more efficient, and more cost-effective than traditional methods. This article discusses the modern methods used for deploying underground communication networks, including microtrenching, directional boring, and horizontal directional drilling. The article also presents the results of deploying these methods and discusses their advantages and limitations.